Nanomaterials in Extreme Environments Fundamentals and Applications - Andrievski, Rostislav; Khatchoyan, Arsen; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book focuses on the behaviour of nanomaterials under extreme conditions of high temperature, irradiation by electron/ions and neutrons as well as in mechanical and corrosion extremes. The theoretical approaches and modeling are presented with numerous results of experimental studies. Different processing methods of extreme-tolerant nanomaterials are described. Many application examples from high-temperature technique, nuclear reactors of new generations, aerospace industry, chemical and general engineering, sensor facility, power engineering, electronics, catalysis and medical preparations are also contained. Some unresolved problems are emphasized.
Preface -- Introduction -- General information on preparation, structure and properties of NM -- Grain growth and behavior at high temperatures -- Irradiation effect of electrons, ions, and neutrons -- Behavior of NM under mechanical extremes -- Behavior of NM in corrosion environments -- Final comments.
Keywords: Nanotechnology; Nanoscience; Materials; Microtechnology; Microelectromechanical systems; Nanotechnology; Nanophysics; Materials Engineering; Microsystems and MEMS